Seleksi Peserta Lomba Paskibraka Menggunakan Metode Hybrid AHP-SAW - Gentur Wahyu Nyipto Wibowo; Saludin Saludin; Lamhot Sitorus; Gogor Christmass Setyawan; Jeperson Hutahaean (Journal of Information System Research (JOSH), 2023)
The competition is an event for the success of a school in showing the success of a school educating their students, one type of competition is the paskibraka competition between schools, the problem that often occurs in the process of selecting prospective participants for the paskibrakan competition is to designate students who are considered to meet the expected competencies, this will have an adverse impact on the consideration of interest, endurance and knowledge of the paskibra so that it is maximal in achieving the expected goals in a competition, subjective selection is considered inappropriate today, it is necessary to make decisions using technological assistance in order to minimize errors in selection process, in this study a decision-making system was used to obtain more structured results in the form of logical calculations, the use of decision support systems has been widely applied o by leaders in making decisions, the logic of decision making is in the form of calculations using the application of decision making methods, one method of application is the Simple Additive Weighting method in finding the value of the data to be selected, and to improve research results so that they are more accurate a combination of weighting methods for consideration such as the method AHP, a combination of methods or AHP-SAW hybrid get the results of 1.0 as the highest value